(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Financial inclusion enables improved and better sustainable economic and social development of the country. It helps in the empowerment of the underprivileged, poor and women of the society with the mission of making them self-sufficient and well informed to take better financial decisions. Financial inclusion takes into account the participation of vulnerable groups such as weaker sections of the society and low income groups, based on the extent of their access to financial services such as savings and payment account, credit insurance, pensions etc. India is a country where a sizeable amount of population lives in rural areas. They are engaged in agriculture and allied activities. Most of the people living in rural and tribal areas are poor. They do not have any access to the banks. The awareness and access of the poor to the banking services is important for the alleviation of the poverty. The aim is to develop a model of an inclusive financial system, which will support full participation of the neglected and unprivileged section of the society in the financial system. The objectives of the study are to assess the banking habits among the people and to examine the financial services awareness among the households residing in rural area of Madhya Pradesh. After analyzing the facts and figures which were collected from the respondents, it can be concluded that majority of the respondents are attached with bank account but are not well prone to all kind of financial services.